Fluorescence Imaging of Extracellular Potassium Ion Using Potassium Sensing Oligonucleotide - Sato, Shinobu; Ohzawa, Shinsuke; Sota, Kojiro; Sakamoto, Naoto; Udo, Ayano; Sueda, Shinji; Matsuda, Tomoki; Nagai, Takeharu; Takenaka, Shigeori (Frontiers in Chemistry, 2022)
Potassium sensing oligonucleotide, PSO, a conjugate of a quadruplex structure-forming oligonucleotide with a peptide incorporating a Förster Resonance Energy Transfer (FRET) chromophore pair, has been developed for fluorescent detection of potassium ion (K+) in aqueous medium. PSO 1 could be introduced into cells for real-time imaging of cytoplasmic K+ concentrations. The introduction of 1 into the cell allowed for real-time imaging of cytoplasmic K+ concentrations. To perform fluorescent imaging of K+ on cell surface, we synthesized twelve PSO derivatives with different types of peptide types and lengths, and oligonucleotide sequences including thrombin binding aptamer (TBA) sequences with FAM and TAMRA as a FRET chromophore pair, and evaluated their performance. 1was shown to respond selectively to K+, not to most ions present in vivo, and to show reciprocal fluorescence changes in response to K+ concentration. For the peptide chains and oligonucleotide sequences examined in this study, the PSO derivatives had Kd values for K+ in the range of 5-30 mM. All PSO derivatives showed high K+ selectivity even in the presence of excess Na+. The PSO derivatives were successfully localized to the cell surface by biotinylated Concanavalin A (ConA) or sulfo-NHS-biotin via streptavidin (StAv). Fluorescence imaging of extracellular K+ upon addition of apoptosis inducers was successfully achieved by 1 localized to the cell surface.